Conservative oxygen therapy in critically ill and perioperative period of patients with sepsis-associated encephalopathy - Li, Yun; Zhao, Lina; Yu, Yang; Zhang, Kai; Jiang, Yi; Wang, Zhiwei; Xie, Keliang; Yu, Yonghao (Frontiers in Immunology, 2022)
Abstract Objectives: Sepsis-associated encephalopathy (SAE) patients in the intensive care unit (ICU) and perioperative period are administrated supplemental oxygen. However, the correlation of oxygenation status with SAE and the targets for oxygen therapy remains unclear. This study aimed to examine the relationship between oxygen therapy and SAE patients. Methods: Patients diagnosed with sepsis 3.0 and in the intensive care unit (ICU) were enrolled. The data were collected between 2008 - 2019 from the Medical Information Mart for Intensive Care IV (MIMIC IV) database and in 2014- 2015 from the eICU Collaborative Research Database (eICU-CRD) database. The generalized additive models were adopted to estimate the oxygen therapy targets in SAE patients and results were confirmed by multivariate Logistic, propensity score analysis, inversion probability-weighting, and doubly robust model and multivariate COX analyses. Survival was analyzed by the Kaplan-Meier method. Results: A total of 10055 patients from eICU-CRD and 1685 from MIMIC IV were included. The incidence of SAE patients was 58.43%. The range of PaO2(97-339)mmHg, PaO2/FiO2 (189-619) and SPO2≥93% may be reduce the incidence of SAE, which were verified by multivariable Logistic regression, propensity score analysis, inversion probability-weighting, and doubly robust model estimation in MIMIC IVdatabase and eICU database. The range of PaO2/FiO2 (189-619) and SPO2≥93% may be reduce the hospital mortality of SAE were verified by multivariable COX regression. Conclusions: SAE patients in ICU, including perioperative period, require conservative oxygen therapy. We may be maintain SpO2≥93%, PaO2 (97-339) mmHg, PaO2/FiO2 (189-619) in SAE patients.